2016
DOI: 10.1371/journal.pone.0166301
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Neopterin Levels Are Associated with Increased Tuberculosis Risk in Rheumatoid Arthritis Patients with QuantiFERON Conversion during Biologic Therapy

Abstract: QuantiFERON-TB-Gold (QFT-G) conversion is frequently observed in rheumatoid arthritis (RA) patients receiving biologic therapy. However, there have not been any known biomarkers available for detecting tuberculosis (TB) in QFT-G converters. We aimed to evaluate clinical utility of cytokines/chemokines for detecting TB in patients with QFT-G conversion. Among a total of 227 RA patients who underwent QFT-G assay, 187 QFT-G-negative patients received biologic therapy without isoniazid prophylaxis. QFT-G assay was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Also, the evaluation of neopterin concentration has clinical value in individuals with HIV infection 36 . In the context of autoimmune disorders, RA shows a high concentration of neopterin accompanied by disease progression; however, this association has not been confirmed among existing data 18 . The results of this meta‐analysis indicated that the concentration of neopterin was increased significantly in RA patients.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Also, the evaluation of neopterin concentration has clinical value in individuals with HIV infection 36 . In the context of autoimmune disorders, RA shows a high concentration of neopterin accompanied by disease progression; however, this association has not been confirmed among existing data 18 . The results of this meta‐analysis indicated that the concentration of neopterin was increased significantly in RA patients.…”
Section: Discussionmentioning
confidence: 75%
“…36 In the context of autoimmune disorders, RA shows a high concentration of neopterin accompanied by disease progression; however, this association has not been confirmed among existing data. 18 The results of this meta-analysis indicated that the concentration of neopterin was increased significantly in RA patients. The pooled analyses revealed a similar rising concentration of neopterin in RA patients with three categories of high, intermediate, and low disease activity scores, which indicates that the neopterin level is not affected by RA progression.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The clinical significance of IGRA conversion and reversion remains uncertain and somewhat confusing for clinicians who may alert toward the possible active TB onset [104], thus inducing to perform additional investigations. In this regard reliable predictors of active TB onset are still lacking [105].…”
Section: Anti-tnfs Biological Therapymentioning
confidence: 99%